Known and potential molecules associated with altered B cell development leading to predominantly antibody deficiencies. Issue 8 (24th July 2021) - Amirifar, Parisa; Yazdani, Reza; Azizi, Gholamreza; Ranjouri, Mohammad Reza; Durandy, Anne; Plebani, Alessandro; Lougaris, Vassilios; Hammarstrom, Lennart; Aghamohammadi, Asghar; Abolhassani, Hassan
Abstract: Predominantly antibody deficiencies (PADs) encompass a heterogeneous group of disorders characterized by low immunoglobulin serum levels in the presence or absence of peripheral B cells. Clinical presentation of affected patients may include recurrent respiratory and gastrointestinal infections, invasive infections, autoimmune manifestations, allergic reactions, lymphoproliferation, and increased susceptibility to malignant transformation. In the last decades, several genetic alterations affecting B‐cell development/maturation have been identified as causative of several forms of PADs, adding important information on the genetic background of PADs, which in turn should lead to a better understanding of these disorders and precise clinical management of affected patients. This review aimed to present a comprehensive overview of the known and potentially involved molecules in the etiology of PADs to elucidate the pathogenesis of these disorders and eventually offer a better prognosis for affected patients.